Effectiveness of cognitive–behavioural therapy on glycaemic control and psychological outcomes in adults with diabetes mellitus: a systematic review and meta‐analysis of randomized controlled trials. Issue 3 (18th August 2016) - Uchendu, C.; Blake, H.
Abstract: Aim: Diabetes is a chronic progressive condition presenting physical, social and psychological challenges that increase the risk of comorbid mental health problems. Cognitive–behavioural therapy (CBT) is effective in treating a variety of psychological disorders, and may potentially improve glycaemic control and psychological outcomes in diabetes. This systematic review and meta‐analysis aims to establish the effectiveness of CBT on glycaemic control and comorbid diabetes‐related distress, depression, anxiety and quality of life in the short, medium and longer term among adults with diabetes. Method: An electronic search was conducted in PubMed, Embase, MEDLINE, PsycINFO, CINAHL, Web of Knowledge, Cochrane Central Register of Controlled Trials and references in reviews. Twelve randomized controlled trials (RCTs) were identified that evaluated the effectiveness of CBT on at least one of: glycaemic control, diabetes‐related distress, anxiety, depression or quality of life in adults with Type 1 or Type 2 diabetes. The Cochrane Risk of Bias Tool and Review Manager version 5.3 were used for risk of bias assessment and meta‐analysis, respectively. Results: CBT is effective in reducing short‐term and medium‐term glycaemic control, although no significant effect was found for long‐term glycaemic control. CBT improved short‐ and medium‐term anxiety and depression, and long‐term depression. Mixed results were found for diabetes‐related distress and quality of life. Conclusion: CBT is beneficial in improving depression for adults with diabetes. It may have benefits for improving glycaemic control and other aspects of psychological health, although the findings are inconclusive.